NUMERICAL ANALYSIS OF AN INVERSE PROBLEM ORIGINATED IN PHENOMENON OF POLLUTION AIR URBAN - Coronel, Anibal (2016)
This paper presents the calibration study of a two - dimensional mathematical model for the problem of urban air pollution. It is mainly assumed that air pollution is aected by wind convection, difusion and chemical reactions of pollutants. Consequently, a convection-diusion-reaction equation is obtained as a direct problem. In the inverse problem, the determination of the diusion is analyzed,assuming that one has an observation of the pollutants in a nite time. To solve it numerically the nite volume method is used, the least squares function is considered as cost function and the gradient is calculated with the sensitivity method.